DISPARITAS PEMIDANAAN DALAM KASUS PERSETUBUHAN TERHADAP ANAK (Studi Kasus Putusan Nomor 140/Pid.Sus/2022/PN.Sgr dan Putusan Nomor 10/Pid.Sus/2023/PN.Sgr,) - Pradistha, Kadek Nandha; Hartono, Made Sugi; Landrawan, I Wayan (Universitas Pendidikan Ganesha, 2024)
This research aims to: (1) find out what factors can cause disparities in cases of sexual intercourse with children that occur in Buleleng Regency. (2) knowing how the judge considered the disparity in decisions No. 140/Pid.Sus/2022/PN.Sgr and No. 10/Pid.Sus/2023/PN.Sgr. The type of research used is empirical legal research with descriptive research characteristics. The location of the research was carried out in Buleleng Regency, namely at the Singaraja District Court Class 1B. The data collection technique used was document study, interviews and observation. The sampling technique used in this research is a non-probability sampling technique with subject determination using the Pruposive Sampling Technique. The data processing and analysis technique uses qualitative. The results of the research show that the factors causing disparities are due to the judge's opinion, statutory factors, public prosecutor law enforcement factors and the defendant's behavior factors in the trial. The judge's considerations in deciding the case are based on the indictment, witness statements, evidence and aggravating and mitigating circumstances. Where the judge decided that in decision No. 140/Pid.Sus/2022/PN.Sgr the defendant was sentenced to 5 years and in decision No. 10/Pid.Sus/2023/PN.Sgr the defendant was sentenced to 2 years.